aInternational-mindednessa:a field of struggle,confusion and hope (Global Journal of Human-Social Science, 2011)
Typically educators of today recognise the importance of international-mindedness and realise that it is in some way related to international education However it has been particularly hard for educators to pin down exactly what international-mindedness is and what its development actually involves This paper examines current literature on the topic of international-mindedness It sets out to illustrate that in the literature on international-mindedness no single narrative account that clearly defines international-mindedness or explains developmental ways of developing it exists Rather many divergent and convergent discourses surround this term creating confusion and unresolved debates related to international- mindedness The paper concludes by highlighting areas that are silenced and places where there are gaps in research and literature on international-mindedness from which proposals for future research can then be contemplated
Keywords: International-mindedness; international education; IB learner profile; International Baccalaureate